Work‐life balance and withdrawal behaviors among knowledge workforce: High performance work system comes into play for managing boundaries - Mathur, Garima; Gulati, Chanda; Sankpal, Shilpa; Kee, Daisy Mui Hung (Global business and organizational excellence, 2024)
In the wake of a turbulent era over the past 3 years, characterized by the unprecedented challenges posed by the COVID‐19 pandemic, individuals have found themselves contending with the intersection of professional and personal responsibilities. The pursuit of luxury has given way to a collective nightmare, as work and family demands converged, each equally relentless and significant. Our paper focuses on the experiences of individuals who confronted and triumphed over these challenges. A sample of 368 professionals, predominantly working from home, was examined to explore the impact of high performance work systems and boundary management in a post‐pandemic landscape marked by blurred boundaries. Our findings support the notion that effective boundary management, encompassing the management of non‐work intruding on work and work encroaching on non‐work, significantly influences withdrawal behaviors. Our study reveals the importance of organizations fostering work practices that empower employees with the IT skills to navigate virtual technologies seamlessly. By doing so, organizations can enhance work‐life balance and mitigate withdrawal behaviors among their workforces.